2003
DOI: 10.4049/jimmunol.171.3.1500
|View full text |Cite
|
Sign up to set email alerts
|

Pellino3, a Novel Member of the Pellino Protein Family, Promotes Activation of c-Jun and Elk-1 and May Act as a Scaffolding Protein

Abstract: Toll-like receptors and the IL-1R are part of the innate immune response aimed at mobilizing defense mechanisms in response to infections or injury. These receptors can initiate common intracellular signaling cascades. One intermediate component in these signaling cascades is Pellino, which was first identified in Drosophila and shown to interact with IL-1R-associated kinase. Two homologues, Pellino1 and Pellino2, have been identified in mammals. A novel member of the Pellino protein family has been identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
102
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(111 citation statements)
references
References 28 publications
7
102
2
Order By: Relevance
“…Three mammalian homologues (Pellino1, 2 and 3) have since been identified, with Pellino3 being expressed in two spliced forms [35][36][37][38][39]. Given that Drosophila Pellino was discovered based on its interaction with Pelle, mammalian Pellino proteins have been characterized by their potential to interact with IRAK molecules.…”
Section: Irak Polyubiquitylation and Tlr/il-1r Signallingmentioning
confidence: 99%
See 4 more Smart Citations
“…Three mammalian homologues (Pellino1, 2 and 3) have since been identified, with Pellino3 being expressed in two spliced forms [35][36][37][38][39]. Given that Drosophila Pellino was discovered based on its interaction with Pelle, mammalian Pellino proteins have been characterized by their potential to interact with IRAK molecules.…”
Section: Irak Polyubiquitylation and Tlr/il-1r Signallingmentioning
confidence: 99%
“…Given that Drosophila Pellino was discovered based on its interaction with Pelle, mammalian Pellino proteins have been characterized by their potential to interact with IRAK molecules. Overexpression studies have shown that mammalian Pellino proteins interact with both IRAK1 and IRAK4 [36,37,[40][41][42][43]. Furthermore, a yeast two-hybrid screen using IRAK4 as bait independently identified Pellino2 as a protein-binding partner [40].…”
Section: Irak Polyubiquitylation and Tlr/il-1r Signallingmentioning
confidence: 99%
See 3 more Smart Citations